POTENSI ANTIOKSIDAN DAN PERSEPSI SENSORI TEH HERBAL BUNGA PEPAYA JANTAN – DAUN STEVIA - Djois Sugiaty Rintjap; Rilyn Novita Maramis; Nivalayanti Gagu; Elisabeth Natalia Barung (Sam Ratulangi University, 2025)
Herbal tea is a food supplement with various health benefits, including antioxidant properties. Herbal tea can be prepared from various parts of plants, one of which is male papaya flowers. The combination of male papaya flowers and stevia leaves is expected to enhance consumer acceptance and the synergistic effects of their biological activities. This study aimed to evaluate the antioxidant activity and sensory perception of male papaya flower (Carica papaya L.) and stevia leaf (Stevia rebaudiana [Bertoni] Bertoni) herbal tea. The study employed a laboratory experimental design. The sample consisted of brewed male papaya flower-stevia leaf herbal tea. Antioxidant activity was evaluated using the DPPH method, while organoleptic evaluation and sensory perception were assessed based on colour, aroma, taste, aftertaste, and overall acceptance. The results demonstrated that male papaya flower-stevia leaf herbal tea possesses antioxidant potential. The addition of stevia leaves to male papaya flower herbal tea improved the taste and aftertaste perception of the herbal tea.